Impact of ex vivo lung perfusion on brain‐dead donor lung utilization: The French experience. Issue 5 (20th January 2022) - Abdoul, Naïssa; Legeai, Camille; Cantrelle, Christelle; Mercier, Olaf; Olland, Anne; Mordant, Pierre; Thomas, Pascal Alexandre; Jougon, Jacques; Tissot, Adrien; Maury, Jean‐Michel; Sage, Edouard; Dorent, Richard
Abstract : Ex vivo lung perfusion (EVLP) is a valuable method for expanding the lung donor pool. Its indications currently differ across centers. This national retrospective cohort study aimed to describe the profile of donors with lungs transplanted after EVLP and determine the effectiveness of EVLP on lung utilization. We included brain‐dead donors with at least one lung offered between 2012 and 2019 in France. Lungs transplanted without or after EVLP were compared with those that were rejected. Donor group phenotypes were determined with multiple correspondence analysis (MCA). The association between donor factors and lung transplantation was assessed with a multivariable multinomial logistic regression. MCA revealed that donors whose lungs were transplanted after EVLP had profiles similar to the donors whose lungs were declined and quite different from those of donors with lungs transplanted without EVLP. Donor predictors of graft nonuse included age ≥50 years, smoking history, PaO2 /FiO2 ratio ≤300 mmHg, abnormal chest imaging, and purulent secretions. EVLP increased utilization of lungs from donors with a smoking history, PaO2 /FiO2 ratio ≤300 mmHg, and abnormal chest imaging. Abstract : Ex vivo lung perfusion has the potential to increase the number of transplantations from donors who have factors that predict lung non‐use.